Digitalization of financial services in the age of cloud - Mina, Jamil; Warda, Armin; Marins, Rafael; Miles, Russ (O'Reilly Media, Inc., 2023)
If you're planning, building, or implementing a cloud strategy that supports digitalization for your financial services business, this invaluable guide clearly sets out the crucial factors and questions to consider first. With it, you'll learn how to avoid the costly and time-consuming pitfalls and disappointments of cloud adoption and take full advantage of the cloud operational model. You'll discover cloud tactics that unlock the benefits of digitalization and how to create a cloud strategy that has the flexibility to streamline operations, integrate channels, and encourage innovation in your firm. Packed with invaluable advice and real-world case studies, this book will show you how to: Select the right operational models for your needs Build resilience into your company's technologies Assess the trade-offs of third-party digital native services versus developing them in-house Ensure operability across cloud services providers Balance innovation and accountability Deal with digitalization issues of particular importance in finance, such as governance, security, and regulatory compliance And more.